Estrategias didácticas para el desarrollo de habilidades socioemocionales en niños de 3 a 5 años - Aucancela Quiñonez, Yamilex Anai (2024)
This research project aims to analyze the impact of didactic strategies on the development of socioemotional skills in children aged 3 to 5 at the Francisco Huerta Rendón Educational Unit. With specific objectives covering the description of strategies, the diagnosis of socioemotional development, and the evaluation of the impact of strategies on meaningful learning, the research focuses on a qualitative approach and a non-experimental design, centered on the observation and description of phenomena in their natural environment. The study population includes 8 teachers and 170 students, with a selected sample of 3 teachers and 30 students from initial education II using non-probabilistic sampling. The descriptive methodology focuses on the analysis of real facts, proposing solutions to identified problems, and using direct observation as a data collection method. The conclusions highlight the importance of continuous training for educators in didactic strategies for socioemotional development. The need to adapt these strategies to the individual needs of each child, implement continuous evaluation systems, and personalize educational activities is emphasized. The recommendations underscore the effectiveness of didactic strategies focused on socioemotional development and the importance of continuous diagnosis to design educational interventions tailored to the individual needs of children.